Nic96p is required for nuclear pore formation and functionally interacts with a novel nucleoporin, Nup188p. - Zabel, Ulrike; Doye, V.; Tekotte, H.; Wepf, R.; Grandi, P.; Hurt, Ed (The journal of cell biology, 1996)
The amino-terminal domain of Nic96p physically interacts with the Nsp1p complex which is involved in nucleocytoplasmic transport. Here we show that thermosensitive mutations mapping in the central domain of Nic96p inhibit nuclear pore formation at the nonpermissive temperature. Furthermore, the carboxyterminal domain of Nic96p functionally interacts with a novel nucleoporin Nup188p in an allele-specific fashion, and when ProtA-Nup188p was affinity purified, a fraction of Nic96p was found in physical interaction. Although NUP188 is not essential for viability, a null mutant exhibits striking abnormalities in nuclear envelope and nuclear pore morphology. We propose that Nic96p is a multivalent protein of the nuclear pore complex linked to several nuclear pore proteins via its different domains.